Literary Theory in the Work of Fernando Lázaro Carreter - Laura Arroyo Martínez (Castilla: Estudios de Literatura, 2014)
This paper is aimed to review and to summarize the main contributions and ideas that Don Fernando Lázaro Carreter made to the field of Literary Theory and Criticism. His initial work on literary stylistics and his subsequent studies on Russian Formalism made him become the founder of this discipline in Spain. Hence his wok arises high interest to the point of being nowadays considered a classic of Philology.